Satellite-Observed Chlorophyll-a Concentration Variability in the East Sea (Japan Sea): Seasonal Cycle, Long-Term Trend, and Response to Climate Index - Park, Kyung-Ae; Park, Ji-Eun; Kang, Chang-Keun (Frontiers in Marine Science, 2022)
In this study, to determine the spatiotemporal variability of satellite-observed chlorophyll-a (Chl-a) concentrations in the East Sea (Japan Sea, EJS), monthly composite images were generated via noise processing using Level-2 MODIS Chl-a data from 2003 to 2020. Harmonic analysis was performed on time-series Chl-a data to present the spatial distribution of seasonal and intraseasonal variability with 1–4 cycles per year. In the EJS, seasonal cycles contributed less than approximately 30% to the total variance in Chl-a variability, indicating the existence of dominant interannual variability. Analysis of the temporal trend in Chl-a concentrations showed that they increased (< 0.06 mg m–3 yr–1) in most of the EJS over almost two decades (2003–2020). In recent years, in the areas showing positive trends in Chl-a, it tended to increase with time, especially in the northern part of the EJS. As a result of examining the trend associated with the physical environment that affects the long-term trend in Chl-a concentrations, sea surface temperature (SST) trends were mostly increased. The wind speeds showed a characteristic strengthening trend in the northeastern part of the EJS and the North Korean coast. Long-term changes in wind direction indicated strengthening of the northerly wind components on the Russian coast and the westerly components on the eastern coast of the Korean Peninsula. These wind changes were closely related to the Arctic Oscillation (AO) index variability in relation to the recent warming of the Arctic Ocean. When the AO index was greater than 1, the wind speed tended to be weakened and the SSTs showed a tendency to increase. This led to general increasing responses in Chl-a concentrations during positive AO. The summer SST anomaly revealed an inverse relationship between higher positive values during the La Niña period and lower ones during the El Niño period. When the amplitude of MEI (Multi-variate ENSO Index) was high (| MEI| > 1), the SST anomaly indicated an inverse correlation with the Chl-a concentration anomaly in the EJS. This study demonstrated the regional effects of climate change on Chl-a variability in the EJS in response to tropical–subtropical and arctic–subarctic interactions between ocean and atmospheric variations.